Political Opportunities in the Samin Movement Against the Establishment of a Cement Factory in Pati - Winda Septiani; Enkin Asrawijaya (Indonesian Association for Public Administration, 2023)
The struggle against the hegemony of rulers and extractive companies is still being carried out by indigenous people around the world. Samin is one of the indigenous populations that is still struggling to defend their territory from the establishment of a cement factory. Through the ideological strength and support from several parties, Samin was able to see a political opportunity to build a resistance movement. This study uses a social movement paradigm, by looking at political opportunities in the resistance movement. This study aims to determine the problems behind the birth of the Samin movement. The research methodology is carried out by in-depth interviews and participatory observation with informants and uses secondary data in the form of information made available in articles or books. The findings show that the active and open resistance carried out by the Samin community was caused by the influence of political opportunities in the reform era. Some actors can mobilize the masses, form organizations, and network broadly so that it is possible for resistance to occur. Actors are also good at raising issues around the destruction of nature, shifts in the social order, inappropriate laws, and threats to livelihood. There is influence from the ideology of past movements in the form of covert resistance which later transformed into modern movements.